2021
DOI: 10.1080/13696998.2021.1965732
|View full text |Cite
|
Sign up to set email alerts
|

Economic value of vaccines to address the COVID-19 pandemic: a U.S. cost-effectiveness and budget impact analysis

Abstract: Declaration of financial/other relationships  WP has served as a paid advisor to Molnlycke Health Care and is a Principal at Monument Analytics, a health care consultancy whose clients include the life sciences industry as well as plaintiffs in opioid litigation. This arrangement has been reviewed and approved by University of Southern California in accordance with its conflict of interest policies.  SM is an employee of Monument Analytics.  NR is an employee of Monument Analytics.  BC is an employee of Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 38 publications
1
85
0
Order By: Relevance
“… 6 Nevertheless, going forward, healthcare systems will need to pay closer attention to the cost effectiveness of interventions for COVID-19. Although some public health measures, such as screening and vaccination programs, have been the subject of economic evaluations, 7 , 8 , 9 , 10 , 11 , 12 , 13 HTA agencies are typically most interested in the value of diagnostic and therapeutic interventions. Evidence from previous pandemics with similar characteristics suggests antiviral treatments may represent a cost-effective use of resources, 14 but assessments specific to COVID-19 are needed.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Nevertheless, going forward, healthcare systems will need to pay closer attention to the cost effectiveness of interventions for COVID-19. Although some public health measures, such as screening and vaccination programs, have been the subject of economic evaluations, 7 , 8 , 9 , 10 , 11 , 12 , 13 HTA agencies are typically most interested in the value of diagnostic and therapeutic interventions. Evidence from previous pandemics with similar characteristics suggests antiviral treatments may represent a cost-effective use of resources, 14 but assessments specific to COVID-19 are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that besides being effective in terms of clinical outcome, COVID-19 vaccines are also able to reduce health care costs by 80% or more ( 19 ). This is in line with our findings, according to which the expenditure for ordinary hospitalizations and ICU admissions of unvaccinated individuals account for 48% of the total expenditure for all hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The mean utility of asymptomatic patients was considered to be equal to that of the general Brazilian population (0.88), progressively decreasing in patients with mild symptoms (0.833), hospitalized in the ward (0.5), hospitalized in the ICU (0.05), and dead (0.0). 24 , 25 …”
Section: Methodsmentioning
confidence: 99%